Premixed Hydrogen/air Flame in Ceramic Granular Bed. (August 2015) - Yang, S.I.; Lin, S.C.
Abstract: This study investigates the characteristics of a lean premixed hydrogen/air flame in a ceramic granular bed (CGB) by conducting experimental measurements and numerical simulations. The experimental results show that the operating range (equivalence ratio, ϕ = 0.2–0.4) of CGBs for flame propagation is smaller than that of free flame due to the laminar flame speed ( S L ), reactivity, and firing rate ( Γ ) of H2 . In addition, flame temperature ( T f ) increases with increasing Γ, but decreases with increasing ϕ . Furthermore, S ab / S L decreases with increasing u ɛ / S L by the fuel characteristic of Hydrogen (H2 ) and heat recirculation in the CGB. The numerical simulation results show that the flame reaction zone in the CGB (porosity, ɛ = 0.33) is greater than that of free flame ( ɛ = 1) because H2 reacts early and changes the flame propagation characteristics.